Stability and forcing of the Iceland-Faroe inflow of water, heat, and salt to the Arctic - B. Hansen; H. Hátún; R. Kristiansen; S. M. Olsen; S. Østerhus (Ocean Science, 2010)
The flow of Atlantic water across the Greenland-Scotland Ridge (Atlantic inflow) is critical for conditions in the Nordic Seas and Arctic Ocean by importing heat and salt. Here, we present a decade-long series of measurements from the Iceland-Faroe inflow branch (IF-inflow), which carries almost half the total Atlantic inflow. The observations show no significant trend in volume transport of Atlantic water, but temperature and salinity increased during the observational period. On shorter time scales, the observations show considerable variations but no statistically significant seasonal variation is observed and even weekly averaged transport values were consistently uni-directional from the Atlantic into the Nordic Seas. Combining transport time-series with sea level height from satellite altimetry and wind stress reveals that the force driving the IF-inflow across the topographic barrier of the Ridge is mainly generated by a pressure gradient that is due to a continuously maintained low sea level in the Southern Nordic Seas. This implies that the relative stability of the IF-inflow derives from the processes that lower the sea level by generating outflow from the Nordic Seas, especially the thermohaline processes that generate overflow. The IF-inflow is an important component of the system coupling the Arctic region to the North Atlantic through the thermohaline circulation, which has been predicted to weaken in the 21st century. Our observations show no indication of weakening.